クロム カンゲン ホウ ニ ヨル スイソ ドウイタイ ヒ ノ ソクテイホウ ト キョクイキ セッピョウ シリョウ ヘノ テキヨウ - 本山, 秀明; モトヤマ, ヒデアキ; 森本, 真司; モリモト, シンジ; 渡辺, 興亜; ワタナベ, オキツグ; Motoyama, Hideaki; Morimoto, Shinji; Watanabe, Okitsugu (2003)
P(論文) 水試料中の水素同位体比を,800度に加熱したクロムによって水試料を水素に還元する方法で測定した.測定精度は1.0‰以内であった.南極氷床上で採取された沿岸から内陸部にかけての表面積雪を測定した.測定範囲は-200‰から-400‰であった.沿岸から内陸へ気温が下がるとともにδDは小さな値となり,この変動はδ^<18>Oと一致した.また過剰重水素が沿岸では10‰以下の小さな値を示すことから,海が近いほど湿潤なところで生成した水蒸気が凝結して降り積もっている雪であると考えられる.地球環境を探るのに有効な水素同位体比の測定法を確立した. We measured the isotope ratio of hydrogen (δD) in melted ice samples by reduction of the water sample with chromium powder. The reproducibility of the δD measurement is within 1.0‰. The δD of surface snow from coast to inland on the Antarctica ice sheet was measured. The measurement range was from -200‰ to -400‰. The δD of surface snow decreased gradually from coast to inland. Variations of δD agree with δ^<18>O fluctuations. The deuterium excess in the coastal region was small, less than 10‰. We established the method of determining δD in melted ice samples, which can be used to investigate the global environment system. departmental bulletin paper